Do Managerial Abilities Influence Organization Member Satisfaction (Evidence From Koperasi Pegawai Negeri Sehati SMK Negeri 3 Tahuna) - Gilly Marlya Tiwow; Christian Habel (AIBPM Publisher, 2018)
This study aims to determine the effect of Management Managerial Ability on Member Satisfaction on Koperasi Pegawai Negeri Sehati SMK Negeri 3 Tahuna. The method used in this study is survey method with Quantitative approach. The data in this study were obtained through questionnaires and interviews. The sample in this study is 31. The data in this study were measured using a Likert scale. Data analysis using Simple Linear Regression. The results of the study indicate that the regression coefficient X is 0.386. The number indicates that every 1% addition to the Management Managerial Ability, the value of member satisfaction increases by 0.386. The positive value indicates positive relationship between Managerial abilities and Organization member satisfaction. Based on the test, the t value is 4.303 bigger than t-table (df n-2) = 2.045. Then H0 is rejected and Ha is accepted. By rejecting H0 and accepting Ha for testing the two variables, it can be concluded that the Managerial Capabilities of the Management affect the members satisfaction of Koperasi pegawai Negeri sehati SMK Negeri 3 Tahuna. Keywords: Managerial Ability, Members satisfaction, Cooperation, regression